Mitophagy as a therapeutic target for exercise-induced fatigue: modulation by natural compounds and mechanistic insights - Yu, Miao; Jiang, Xiujuan; Zhang, Yingxin; Zhang, Wensi; Wang, Tianlong; Wang, Jialin; Shao, Junwei; Zhang, Lixin; Sun, Yiting; Meng, Xianglong; Li, Xiaohong; Liu, Xianjun (Frontiers in Physiology, 2025)
Exercise-induced fatigue is closely associated with mitochondrial dysfunction, and mitophagy plays a critical role in maintaining mitochondrial homeostasis by clearing damaged mitochondria and reducing oxidative stress. This review systematically summarizes current evidence on the regulatory mechanisms of mitophagy in exercise-induced fatigue, particularly through pathways such as PINK1/Parkin, BNIP3/Nix, FUNDC1, and AMPK, and examines how natural compounds including sulforaphane, Rhodiola crenulata, ginseng, modulate these pathways to alleviate fatigue. These findings suggest the presence of mitophagy threshold in different models and highlight its potential as a therapeutic target for fatigue management. Ultimately, this review proposes novel strategies for developing natural anti-fatigue agents based on mitophagy regulation, while underscoring the need for further mechanistic studies in diverse physiological and pathological settings.